Pengaruh Biaya Operasional Pendapatan Operasional (BOPO) Dan Non Performing Financing (NPF) Terhadap Profitabilitas Pada Perbankan Syariah Yang Terdaftar Di BEI - Rostinah; Nafisah Nurulrahmatiah; M. Rimawan (Indo Publishing, 2025)
The purpose of this study is to analyze the effect of operating income costs (BOPO) and non-performing financing (NPF) on profitability in Islamic banks listed on the IDX. This study was conducted on the Indonesia Stock Exchange (IDX) with Islamic banks as the object. The research data was obtained by downloading financial reports through annual reports, financial reports on the website www.idx.co.id, and the official websites of the banks that were the subjects of the study. The unit of analysis in this study was Islamic banks listed on the IDX in 2019-2023. The instruments used in this study were tables in the form of financial reports consisting of balance sheet and income statement data in the form of data on non-performing loans, total financing, operating expenses, operating income, net profit, and total assets for 5 years, namely from 2019 to 2023. The population in this study was all Islamic banks listed on the IDX from 2019 to 2023, totaling four banks. The sample in this study consisted of three Islamic banks listed on the IDX from 2019 to 2023. The sampling technique used was purposive sampling. The data collection techniques used in this study were documentation and literature study. The data analysis techniques used were classical assumption testing, multiple linear regression analysis, multiple correlation coefficient, determination test, t-test, and u-test. The results indicate that the Cost of Operating Income (BOPO) and Non-Performing Financing (NPF) have a simultaneous significant effect on Return On Assets (ROA) in Islamic banks listed on the IDX.